PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH KOTA PONTIANAK PROVINSI KALIMANTAN BARAT TAHUN 2016 - Sujendra, Bima (JURNAL BORNEO AKCAYA, 2016)
Public Participation in Local Government Planning Work Pontianak province of West Kalimantan in 2016 was chosen because the researchers are encouraged by the phenomenon of community participation in implementation RKPD Musrenbang for the preparation of the proposal is still lacking and many people who do not direalisaikan. To that end, the general research problem is formulated: "How can public participation in the Development Plan Local Government of West Kalimantan Province Pontianak Year 2016". The study design used a qualitative approach. The results showed that community participation in providing information about the conditions, needs and attitudes in preparation RKPD 2016 that have not responded by the City Government through Bapedda, community involvement in the preparation and planning preparation RKPD Year 2016 in order to generate trust and a sense of community has also not been successful optimally, and public participation in the utilization of democratic rights in the implementation of Musrenbang RKPD still lacking, so the implementation of the present society Musrenbang more impressive work in vain or simply fulfill a formality or a mechanism to meet the requirements set out in legislation.